Screening of Some Soybean (Glycine max L. Merrill) Genotypes for Resistance Against Major Insect Pests - Murry, L.; L, Imtinaro; Jamir, T. (International Journal of Bio-resource and Stress Management, 2018)
A study was conducted in the experimental Research Farm of NU: SASRD, during Kharif,2016 in order to screen some soybean genotypes for resistance against some major insect pests of soybean using two replications. Thirty-five genotypes (TS 80, JS 21-08, VLS 92, PS 1589, MACS 1543, DS 3105, SL 1104, KDS 1045, DSb 32, RVS 2009-9, MACS 1520, PS 1587, NRC 126, RSC 10-70, KDS 921, Himso 1687, MAUS 711, NSO 626, AMS-MB 5-19, NRC 125, RSC 10-71, PS 1086, TS 70, VLS 93, NRC 127, SL 1113, DS 3106, BAU 100, RSC 10-52, NRC 124, AMS-MB 5-18, MACS 1505, KDS 980, DSb 31 and JS 21-05) of soybean along with three check varieties (JS 7152, RKS 18 and JS 335) were used for the study. The major insect pests observed were whitefly (Aleurodicus dispersus), leaf webber (Anarsia ephippias), flea beetle (Systena sp.) and stink bug (Nezara viridula). A separate reading was maintained for each of the soybean genotypes. Insect pests that occurred were recorded at fifteen days interval starting from seven days after germination which was continued till harvest. The genotype DS 3105 (17.25 ten plants-1) and BAU 100 (5.25 ten plants-1) showed highest and lowest infestation by whitefly, respectively. On leaf webber, the highest infestation was found on JS 21-08(4.05 metre row length-1) and lowest was found on JS 335 (0.32 metre row length-1). In case of flea beetle, DS 3106(4.80 metre row length-1) showed highest infestation while lowest infestation was found on NSO 626(1.63 metre row length-1). The genotypes RSC 1052(5.9 metre row length-1) and NRC 124 (5.9 metre row length-1) reported highest infestation and TS 80(0.4 metre row length-1) reported lowest infestation by stink bug.